Identification and antibiotic susceptibility of Gram-positive bacteria exhibiting β-hemolysis isolated from traditional pig farms in Bali, Indonesia - I Wayan Suardana; Ienioliski L. O. Rohi Bire; Komang Januartha Putra Pinatih (Universitas Airlangga, 2026)
Pig farming in Bali plays a critical role from a One Health perspective, as zoonotic cases originating from pigs have been documented, including human infections caused by Gram-positive bacteria such as Streptococcus suis. Furthermore, farmers in affected areas often administer medications, including amoxicillin, chloramphenicol, and streptomycin, without adhering to appropriate dosages, treatment durations, or disease-specific indications. Considering the complexity of this issue, the identification of β-hemolytic Gram-positive bacteria isolated from traditional pig farms in Bali is warranted to address public health concerns. This study began with the cultivation of eight bacterial isolates obtained from the tonsils and nasal cavities of pigs on blood agar media. Subsequent analyses included Gram staining and catalase, oxidase, and salt tolerance testing. Molecular identification was performed through 16S rRNA gene analysis. Antibiotic susceptibility testing was conducted using the Kirby–Bauer disk diffusion method. The results indicated that all eight isolates were Gram-positive and exhibited β-hemolysis. Molecular identification revealed that six isolates were Enterococcus faecalis, one isolate was classified as Staphylococcus spp., and one isolate as E. casseliflavus. Antibiotic susceptibility testing demonstrated that all isolates remained sensitive to amoxicillin, chloramphenicol, and streptomycin. Nevertheless, the prudent use of antibiotics remains essential to prevent zoonotic transmission and the development of antimicrobial resistance.